Multifocal Langerhans Cell Histiocytosis: A Unique Presentation of Eosinophilic Granuloma with Intracranial Extension, Massive Lymphadenopathy, and Epstein-Barr Viral Infection in an Adolescent Female - Kent Wade Foster; Shamika Kayo Robinson; Eleanor Tung-Hahn; George Gibbons; Carl Wayne Cruse; Kumaran Mudaliar; Rebecca Tung; Wendy Kim (Karger Publishers, 2021)
We report the case of an otherwise healthy 17-year-old female who presented for surgical removal of an enlarging "atypical cyst" on her scalp. During subtotal excision, only friable serosanguinous translucent ribbons of tissue were found. A histopathologic diagnosis of Langerhans cell histiocytosis (LCH) was rendered and imaging studies revealed extradural invasion of the tumor. Within weeks, the patient also developed progressive lymphadenopathy with grossly elevated levels of Epstein-Barr virus viral capsid antigen antibody levels. This report aims to highlight a unique presentation of LCH with discussion of workup, management, and avoidance of potential surgical complications.